Advances in measuring DNA methylation. Issue 1 (6th January 2022) - Sun, Ruixia; Zhu, Ping
Abstract : Abstract: DNA methylation is one of the most important components of epigenetics, which plays essential roles in maintaining genome stability and regulating gene expression. In recent years, DNA methylation measuring methods have been continuously optimized. Combined with next generation sequencing technologies, these approaches have enabled the detection of genome-wide cytosine methylation at single-base resolution. In this paper, we review the development of 5-methylcytosine and its oxidized derivatives measuring methods, and recent advancement of single-cell epigenome sequencing technologies, offering more referable information for the selection and optimization of DNA methylation sequencing technologies and related research.